Heterogeneity of malaria transmission in urban settings in Ethiopia: A seroprevalence and risk factor analysis - Teka, Hiwot; Fekadu, Saron; Ejigu, Legesse Alamerie; Sisay, Solomon; Abdo, Melat; Demisse, Mulugeta; Mamo, Hassen; Drakeley, Chris; Byrne, Isabel; Medhin, Girmay; Golassa, Lemu; Gadisa, Endalamaw; et al. (PLOS ONE, 2026)
Malaria remains a significant public health concern in Ethiopia, affecting both rural and urban populations. In urban settings, rapid unplanned expansion, poor drainage, and population movement are increasingly creating aquatic habitats that support vectors such as Anopheles stephensi, thereby leading to complex and underestimated transmission patterns. Serology-based risk factor analyses offer a sensitive indicator of recent and past exposure, helping to reveal underlying transmission patterns and more tailored interventions. This study assessed malaria seroprevalence and associated risk factors among residents of three towns in Ethiopia: Adama, Metehara, and Awash Sebat Kilo to better characterize transmission dynamics and identify context-specific vulnerabilities. A community-based cross-sectional survey was conducted from January 30 to March 14, 2020, involving 912 individuals from randomly selected 196 households. Malaria infection was diagnosed using rapid diagnostic tests (RDTs) and quantitative polymerase-chain reaction (qPCR). Serological analyses were performed to determine exposure to Plasmodium falciparum and Plasmodium vivax. The study found a low malaria prevalence of 0.78% by RDT and 4% by qPCR, with 1.7% of cases due to P. falciparum and 2.3% due to P. vivax. The overall seroprevalence was 19.4% (149/767) for P. falciparum and 18% (139/767) for P. vivax using combined short-lived response markers. Seroprevalence rates varied among towns, with Awash Sebat Kilo showing the highest exposure for recent markers (36.5% for P. falciparum; 28% for P. vivax) compared to lower rates in Adama (2.8% and 2.8%, respectively). Proximity to breeding sites (OR = 2.8, 95% CI: 1.1–7.4; p = 0.037) and being older than 15 years (OR = 4.0 95% CI: 2.1–7.6; p < 0.001) were significant risk factors for P. falciparum and P. vivax malaria exposure, respectively. This study demonstrates marked heterogeneity in malaria exposure across urban settings, with the lowest seroprevalence observed in Adama and higher levels in Awash Sebat Kilo. The findings emphasize the importance of incorporating serological surveillance into routine monitoring and highlight the need for targeted, locally tailored control strategies. Such tailored approaches will be increasingly critical, particularly in the context of emerging urban transmission risks driven by the expansion of An. stephensi in the region.